2013
DOI: 10.1073/pnas.1309906110
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of reactivation of latent herpes simplex virus 1 in ganglionic organ cultures by p300/CBP and STAT3

Abstract: A key property of herpes simplex viruses (HSVs) is their ability to establish latent infection in sensory or autonomic ganglia and to reactivate on physical, hormonal, or emotional stress. In latently infected ganglia, HSV expresses a long noncoding RNA and a set of microRNAs, but viral proteins are not expressed. The mechanism by which latent HSV reactivates is unknown. A key question is, what is the mechanism of reactivation in the absence of tegument proteins that enable gene expression in productive infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 45 publications
1
45
0
Order By: Relevance
“…Total RNAs were extracted from murine trigeminal ganglia (TG) harboring latent viruses or from infected cells by the mirVana miRNA Isolation Kit (Ambion) or TRIzol reagent (Invitrogen) according to the manufacturer's instructions and earlier reports (32,33). Murine model studies of HSV-1 latent infection and reactivation were performed at the University of Chicago as described elsewhere (32), according to protocols approved by the Institutional Animal Care and Use Committee of the University of Chicago.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNAs were extracted from murine trigeminal ganglia (TG) harboring latent viruses or from infected cells by the mirVana miRNA Isolation Kit (Ambion) or TRIzol reagent (Invitrogen) according to the manufacturer's instructions and earlier reports (32,33). Murine model studies of HSV-1 latent infection and reactivation were performed at the University of Chicago as described elsewhere (32), according to protocols approved by the Institutional Animal Care and Use Committee of the University of Chicago.…”
Section: Methodsmentioning
confidence: 99%
“…In medium containing NGF and EGF, the virus remains silent for ∼18-24 h. Studies on this model revealed that in ganglia maintained in medium containing NGF plus EGF, the virus is maintained in a dynamic equilibrium that is disrupted by inhibitors of HDAC-1 and -4, the PI3K-AKT-mTOR and STAT3 pathways, or proapoptotic drugs (10,11). Reactivation in medium containing anti-NGF antibody is inhibited by the expression of REST or by a p300/CBP inhibitor (11,12). Perhaps more significant for reactivation, in neurons all genes are expressed at once rather than sequentially in a coordinated fashion as is seen in infected cells at the portal of entry.…”
mentioning
confidence: 99%
“…Indeed, HSV establishes latency in neurons that depend on NGF and incubation with NGF and epidermal growth factor delays HSV reactivation [13][14][15][16][17]. Moreover, blocking of NGF with antibodies or depletion of NGF results in HSV reactivation in vitro, ex vivo and in animal models [17][18][19][20][21][22][23]. An explanation for this could be the trigger of caspase 3-dependent apoptosis following NGF depletion [23][24][25].…”
Section: /3mentioning
confidence: 99%
“…Moreover, blocking of NGF with antibodies or depletion of NGF results in HSV reactivation in vitro, ex vivo and in animal models [17][18][19][20][21][22][23]. An explanation for this could be the trigger of caspase 3-dependent apoptosis following NGF depletion [23][24][25]. However, the molecular mechanisms leading to reactivation seem to differ when apoptosis is triggered in the presence of NGF [26].…”
Section: /3mentioning
confidence: 99%
See 1 more Smart Citation